Identification of Small-Molecule Inhibitors of Hyperpolarization-Activated Cyclic Nucleotide–Gated Channels. (October 2015) - Han, Ye; Lyman, Kyle; Clutter, Matt; Schiltz, Gary E.; Ismail, Quratul-Ain; Prados, Diego Bleifuss; Luan, Chi-Hao; Chetkovich, Dane M.
Hyperpolarization-activated cyclic nucleotide–gated (HCN) channels function in the brain to limit neuronal excitability. Limiting the activity of these channels has been proposed as a therapy for major depressive disorder, but the critical role of HCN channels in cardiac pacemaking has limited efforts to develop therapies directed at the channel. Previous studies indicated that the function of HCN is tightly regulated by its auxiliary subunit, tetratricopeptide repeat–containing Rab8b interacting protein (TRIP8b), which is not expressed in the heart. To target the function of the HCN channel in the brain without affecting the channel's function in the heart, we propose disrupting the interaction between HCN and TRIP8b. We developed a high-throughput fluorescence polarization (FP) assay to identify small molecules capable of disrupting this interaction. We used this FP assay to screen a 20, 000-compound library and identified a number of active compounds. The active compounds were validated using an orthogonal AlphaScreen assay to identify one compound (0.005%) as the first confirmed hit for inhibiting the HCN-TRIP8b interaction. Identifying small molecules capable of disrupting the interaction between HCN and TRIP8b should enable the development of new research tools and small-molecule therapies that could benefit patients with depression.